2012
DOI: 10.3892/mmr.2012.877
|View full text |Cite
|
Sign up to set email alerts
|

Foxp3 expression in A549 cells is regulated by Toll-like receptor�4 through nuclear factor-κB

Abstract: Abstract. Foxp3 is a master regulator of the development and function of CD4 + CD25 + regulatory T cells (Tregs). Previous studies have reported that Foxp3 is also expressed in tumour cells and promotes tumour immune evasion. However, the regulation of the expression of Foxp3 in tumour cells remains unclear. Toll-like receptor 4 (TLR4), a member of the pattern recognition receptor family, is also expressed in tumour cells. Previous studies have found that the TLR4 signaling pathway is involved in tumour immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…During this maturation neutrophils also attain their nuclear lobular morphology ( 19 ). The formation of granules inside the developing neutrophils starts between the myeloblast and promyelocyte stage and different granules are formed at different steps of the maturation process ( 20 ). A large pool of mature neutrophils is present in bone morrow from where they can be rapidly released into the circulation in response to infectious, inflammatory or tissue damage associated stimuli ( 21 ).…”
Section: Definition Properties and Life Cycle Of Neutrophilsmentioning
confidence: 99%
“…During this maturation neutrophils also attain their nuclear lobular morphology ( 19 ). The formation of granules inside the developing neutrophils starts between the myeloblast and promyelocyte stage and different granules are formed at different steps of the maturation process ( 20 ). A large pool of mature neutrophils is present in bone morrow from where they can be rapidly released into the circulation in response to infectious, inflammatory or tissue damage associated stimuli ( 21 ).…”
Section: Definition Properties and Life Cycle Of Neutrophilsmentioning
confidence: 99%
“…Furthermore, arginine is essential for the generation of nitric oxide by macrophages, an essential component of the innate immune response. In contrast, methionine has an important role in the growth, development and histological structure of immune organs and enhances macrophage phagocytic activity ( 62 ). Methionine deficiency also decreases lymphocyte activities and inhibits the proliferation and differentiation of B and T cells ( 63 ).…”
Section: Physical Inactivity Malnutrition and Covid-19mentioning
confidence: 99%
“…A healthy immune system may aid the prevention and treatment of patients with COVID-19 ( 62 ). Vitamins play an important role in normal immune function and their dietary levels tightly regulate immune reactions ( 66 ) ( Table 1 ).…”
Section: Physical Inactivity Malnutrition and Covid-19mentioning
confidence: 99%
“…However, Chu et al demonstrated that FOXP3 depletion downregulated cyclin D1 and NF-κB subunit p65, but upregulated caspase-3 levels in K1 and WRO thyroid cancer cells [182]. Also, Jia et al indicated that blockade of toll-like receptor 4 (TLR4) signaling induced downregulation of FOXP3 after blocking NF-κB in A549 cells [183]. Here microenvironmental conditions where FOXP3 acts as a tumor suppressor or an oncogene should be clearly determined in specific cancers in association with TRL4, NFAT and NF-κB signaling in the future.…”
Section: The Interplay Between Foxp Family Members and Other Moleculesmentioning
confidence: 99%